2016
DOI: 10.1002/anie.201606574
|View full text |Cite
|
Sign up to set email alerts
|

Limiting Perovskite Solar Cell Performance by Heterogeneous Carrier Extraction

Abstract: Although the power conversion efficiency of perovskite solar cells has improved rapidly, a rational path for further improvement remains unclear. The effect of large morphological heterogeneity of polycrystalline perovskite films on their device performance by photoluminescence (PL) microscopy has now been studied. Contrary to the common belief on the deleterious effect of morphological heterogeneity on carrier lifetimes and diffusivities, in neat CH NH PbI (Cl) polycrystalline perovskite films, the local (int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
67
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(74 citation statements)
references
References 37 publications
6
67
1
Order By: Relevance
“…We note that it is one of the longest PL lifetime reported for MAPbI 3 films . The close‐to monoexponential decay also indicates that there are fewer nonradiative defects inside the MAPbI 3 films prepared via the chloroform‐assisted HCl method . As the aging process most probably eliminates defects related to the presence of excess DMF and HCl inside MAPbI 3 films, such defects might be removed completely during anti‐solvent washing process.…”
Section: Resultsmentioning
confidence: 67%
“…We note that it is one of the longest PL lifetime reported for MAPbI 3 films . The close‐to monoexponential decay also indicates that there are fewer nonradiative defects inside the MAPbI 3 films prepared via the chloroform‐assisted HCl method . As the aging process most probably eliminates defects related to the presence of excess DMF and HCl inside MAPbI 3 films, such defects might be removed completely during anti‐solvent washing process.…”
Section: Resultsmentioning
confidence: 67%
“…Our group has previously demonstrated that confocal PL maps, when measured at excitation densities below the local trap density (~10 15 cm -3 to ~10 17 cm -3 ), 12,[53][54][55] can reflect the local trap distribution in the film. 12,13 Although carrier diffusion is still important, 13,56 under such conditions, high PL intensities correspond to regions with lower trap density, and low PL intensities to regions with higher trap density. 13…”
Section: The Grains Are Identified Using 4֯ As the Threshold (B) Kmentioning
confidence: 99%
“…Fluorescence imaging of MAPbBr 3 MCs (Figure 1b) reveals spatially non-uniform emission from individual grains,w ith higher intensity at the edges compared to that at the interiors,s imilar to recent reports on other perovskites. [21][22][23] Such contrasting behaviour is likely due to differences in electronic structure and radiative recombination dynamics at the boundaries and interior regions of MCs.More interestingly,wefind that PL intensity of each MC fluctuates dramatically with time (see Movie M1, Supporting Information), exemplified in Figure 1c using sequential images (over 8sat 1sintervals) for two MCs (MC-1 and MC-2). TheP L intensity trajectories for entire MAPbBr 3 MCs (Figure 1d) reveal sudden jumps between various dim and bright levels on top of as low (< 1Hz) time-varying base intensity.T he recurrence of high frequency (> 10 Hz) prominent PL fluctuations is validated using intensity jump distributions for each MC (Figure 1e), which have significantly larger width compared to that for the background noise.W e designate abrupt (40-80 ms) intensity jumps with amplitudes more than five times the standard deviation of the background fluctuations (ca.…”
Section: In Memory Of Professor Mihir Chowdhurymentioning
confidence: 99%